A Tumor-Like Lesion Mimicking Mucinous (Colloid) Carcinoma in Heterotopic Pancreas of the Prepyloric Antrum: A Formidable Challenge for Frozen Examination - Teke, Zafer; Zengin, Neslihan Inci; Atalay, Fuat; Karaman, Kerem; Demirbag, Ali Eba; Akdogan, Meral (JOP. Journal of the Pancreas, 2010)
Context Heterotopic pancreas is defined as the presence of pancreatic tissue, outside its usual location, which lacks anatomical and vascular continuity with the pancreas proper. Despite the development of modern diagnostic procedures, it is still difficult to differentiate heterotopic pancreas from benign or malignant tumors and other tumor-like lesions. Frozen examination of mucinous lesions arising from heterotopic pancreas may represent a diagnostic problem. A decision may be very difficult and it is sometimes impossible to decide on the basis of the frozen sections whether a lesion is benign or malignant. Case report We report a tumor-like lesion mimicking a mucinous (colloid) carcinoma arising in heterotopic pancreatic tissue in the prepyloric antrum of a 56-year-old woman which was found incidentally during an elective laparoscopic cholecystectomy for cholelithiasis. The tumor was treated by wedge resection and, in the frozen section examination, there were pancreatic ducts in the proper muscle layer, pancreatic acini with islets of Langerhans under the serosal surface and mucinous lakes close to the heterotopic pancreatic tissue and to a peripheral nerve. Conclusion The significance of this unusual lesion is its potential confusion with mucinous (colloid) carcinoma or other mucous tumors. Such confusion is more likely to occur if the tissue sample is selective or limited, and the presence of pancreatic tissue cannot be verified. Therefore, we believe that a choice of local excision, wedge resection or more extensive eradication be determined only after intraoperative, pathological confirmation of the complete and accurate diagnosis. Image: Intraoperative laparoscopic appearance of prepyloric antral lesion.